ANALISIS MOTIVASI, KEPUASAN, KUALITAS SERTA EFEKTIVITAS KERJA DI DALAM PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN PADA PT. PELAYARAN NASIONAL INDONESIA - Utami, Susiati Purwaning (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
The efforts to reach company goals depends very much on the ability of its leaders in moving the Organization towards a predetermined. Several factors affect the improvement of work productivity of employees. Several factors affect the improvement of work productivity of employees. The purpose of this research was to know (1) the influence of labor motivation towards work productivity of employees, (2) the influence of job satisfaction of employee productivity, (3) the influence of the quality of work of the employee productivity (4) influence the effectiveness of the work of the employee work productivity (5) How far is the influence of motivation, satisfaction, quality and effectiveness of work simultaneously towards work productivity of employees. This research was conducted at PT PELNI, the moving on ocean freight services that give priority to the contribution of income for the State, employees, as well as play a role in environmental development as well as service to the community. The method used is quantitative, with a population of 789 and an employee of PT PELNI, and sample as many as 90 people random employees. Technique of data analysis using regression and correlation, and the hypothesis test. The results showed that: (1) there is a strong and significant positive relationship between motivation towards work productivity of employees of PT PELNI (2) there is a strong and significant positive relationship between employee satisfaction to productivity of PT PELNI (3) there is a strong and significant positive relationship between quality of work productivity of employees of PT PELNI (4) there is a strong and significant positive relationship between the effectiveness of work productivity of employees of PT PELNI (5) there is a strong and significant positive relationship simultaneously between motivation, satisfaction, quality of work, towards the effectiveness of employee productivity PT PELNI.